A Conceptual Framework of Human Resource Technology Transfer (HRTT) - Mohammad Abdul Jabber (Academic Journal on Science, Technology, Engineering & Mathematics Education, 2021)
HR technologies are playing a pivotal role in shaping organizational HR practices and organizational strategies. HR Technologies are helping HR functions in such a way where the HR became a decision science with a measurable impact on business results. Now the non-HR professionals are implementing HR function at ease with the help of HR technologies. As a result, there is immense use of HR technologies in both larger and smaller organizations. The hiking demand of HR technologies and its innovation requires a model for effective HR technology transfer (HRTT). Moreover, there is a strong need for making a proper balance among the applications, implementations, usages and development of HR technologies which depends on the successful and effective HR technology transfer. This paper thus proposes a model on HR technology transfer and finds out the actors and their characteristics. A better understanding of these actors and a national policy level development will help to make an effective HR technology transfer and hence the development of the HR functions and the organizations.